Transient grating spectroscopy of thermal diffusivity degradation in deuterium implanted tungsten - Reza, A; Zayachuk, Y; Yu, H; Hofmann, F (Elsevier, 2019)
Using transient grating spectroscopy, we measure thermal diffusivity and surface acoustic wave speed in tungsten exposed to different fluences of deuterium plasma. Scanning electron microscopy (SEM) shows the formation of surface blisters that have similar morphology for all fluences considered. A significant reduction in thermal diffusivity and surface acoustic wave speed occurs as a result of plasma exposure. A saturation of the thermal diffusivity reduction with fluence is seen. Deuterium ion flux density appears to play a more important role in thermal diffusivity reduction than exposure time. These observations have important implications for plasma facing components in future fusion reactors.